BREAST CANCER IN MEN: CLINICAL FEATURES AND DISEASE COURSE (Western European Journal of Medicine and Medical Science, 2026)
Male breast cancer (MBC) is a rare but clinically significant malignancy that accounts for less than 1% of all breast cancer cases worldwide. Due to its low incidence and limited public awareness, diagnosis is often delayed, resulting in more advanced disease at presentation compared to female breast cancer. This paper reviews the clinical features, risk factors, diagnostic challenges, and disease course of breast cancer in men. It also analyzes current literature on epidemiology, pathology, treatment approaches, and prognosis. Understanding the unique clinical and biological characteristics of male breast cancer is essential for improving early detection, management strategies, and patient outcomes.